Caracterização geoquímica e mineralógica de folhelhos aplicada à exploração de gás e óleo em reservatórios não convencionais : formações Irati e Palermo (bacia do Paraná) no Rio Grande do Sul - Ramos, Alessandro da Silva (2014)
The search for the exploration and production of gas in unconventional reservoirs such as shale gas (shale gas) means a possibility of better use of energy resources in Brazil. While the global energy dynamics, through natural resources, technological advances, markets and institutions that shape today, determine the energy of tomorrow. However, shale gas production has a shorter life cycle, so it can be stated that provides a rapid return on investment, unlike the production of conventional reservoirs with return medium to long term. From this perspective, an analysis of geochemical and mineralogical parameters of shales of the Irati and Palermo formations for hydrocarbons research (oil and gas) will be held in the areas studied, estimating the geochemical and mineralogical potential of these targets for oil reservoirs and unconventional gas. The geochemical and mineralogical parameters to be analyzed and studied for the evaluation are: mineral matter by gravimetric analysis measuring the remaining mineral content after combustion, elemental composition (by total organic carbon analysis (TOC), total carbon (TC), hydrogen (H) and total sulfur (TS)) and clay (by infrared spectroscopy, scanning electron microscopy (SEM) and X-ray diffraction (XRD), moreover, the methane adsorption capacity of will be assessed in shales). Through the study of the elemental analysis in Irati shale formations and Palermo, it was found that the potential for hydrocarbon generation is found medium and medium to high, respectively. In addition, the main clay minerals present in the reservoirs in Irati formations and Palermo are: illite, kaolinite, smectite and chlorite, but also observed the presence of minerals such as quartz and pyrite Formation for Palermo, as well as quartz and analcime to Irati Formation. Thus, the results obtained for sample adsorption formation Palermo (238.50 m depth) was 13.72 cm³/g, for the samples of Irati (m depths of 95.30, 107.50 and 218.45) were 6.17 cm³/g, 4.61 cm³/g and 11.73 cm³/g.